A bespoke low‐cost system for radio tracking animals using multi‐rotor and fixed‐wing unmanned aerial vehicles. Issue 11 (28th August 2020) - Roberts, Benjamin; Neal, Mark; Snooke, Neal; Labrosse, Frédéric; Curteis, Tristan; Fraser, Mariecia
Abstract: Due to the costs of related technologies, tracking studies typically use low numbers of animals as representative samples for whole group or species analysis, often without clear knowledge as to how representative these numbers are. The use of unmanned aerial vehicles (UAVs) has the potential to considerably improve radio‐frequency (RF)‐based tracking systems. This includes improved line‐of‐sight visibility, access and range in difficult terrain and an increase in achievable spatial accuracy. This paper presents details of a fully custom‐built active RF identification tag and receiver system bespoke to UAVs, compatible with both multi‐rotor and fixed‐wing platforms. Using sheep as a model, we show the suitability of this system for tracking large terrestrial mammals. During static testing using both platform types, we calculated a spatial accuracy of 58.5 m (based on 95th percentile/R95 parameter) for this system using data from 14 flights ( n = 175 tag interactions). When tested on sheep, working tags were detected 93% of the time over seven conducted flights. We provide practical considerations for operating this system on a UAV platform, address concerns relating to the system and identify future areas of research both for this system and other UAV‐based RF tracking systems.